Hydrogenetic Fe-Mn Crusts From The Atlantic And Pacific Oceans: Geological Evolution And Conditions Of Formation - Irina A. Pulyaeva (International Marine Minerals Society, 2011)
Hydrogenetic Fe-Mn crusts are ubiquitous in the ocean basins and play an important role in marine mineral-deposit research because of their widespread occurrence and high concentrations of valuable and rare metals. Directed research, which started in the last quarter of the 20th century, has provided significant results, with substantial amounts of data produced on Fe-Mn crusts structure, composition, and distribution in the global ocean. Detailed study of several seamounts has given confidence about the scale of Fe-Mn crust development and their characteristics. Now, commercial interests gain more and more attention. However, at the same time some theoretical questions related to Fe-Mn crust history including controls on metal sources and concentrations have not yet been answered. Here, we present the overview of age, composition, distribution, and geological setting of hydrogenetic Fe-Mn crusts from Pacific and Atlantic seamounts and discuss the geological evolution and conditions that led to the formation of potentially economic concentrations of metals. The age, composition, and distribution of Fe-Mn crusts in the Atlantic and Pacific oceans were determined by using a Fe-Mn deposits database compiled from our original data, published papers, published databases, and other international sources. Comparative analysis of Fe-Mn deposits from the Atlantic and Pacific oceans shows that there are similarities in basic characteristics of crust formation in both oceans. Simultaneously, there are significant differences in the scale of Fe-Mn crust distribution and composition that can be explained by differences in geological settings and characteristics of the deposition environment.